2022
DOI: 10.3390/ijerph19053012
|View full text |Cite
|
Sign up to set email alerts
|

Role of Empathy and Lifelong Learning Abilities in Physicians and Nurses Who Work in Direct Contact with Patients in Adverse Working Conditions

Abstract: Empathy and lifelong learning are two professional competencies that depend on the four principles of professionalism: humanism, altruism, excellence, and accountability. In occupational health, there is evidence that empathy prevents work distress. However, in the case of lifelong learning, the evidence is still scarce. In addition, recent studies suggest that the development of lifelong learning varies in physicians and nurses and that it is sensitive to the influence of cultural stereotypes associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
3
5
0
Order By: Relevance
“…The higher the level of ego depletion was, the stronger the work alienation. Our results supported previous studies that showed that empathy was negatively correlated with ego depletion and work alienation, while ego depletion was positively correlated with work alienation ( Finley et al, 2017 ; Delgado Bolton et al, 2022 ). Nurses with high empathy could correctly perceive their own emotions and those of their patients, reasonably and effectively regulate their cognition, emotion, and behavior, reduce their energy consumption, get along well with patients, and experience a better sense of value and achievement in their work.…”
Section: Discussionsupporting
confidence: 92%
“…The higher the level of ego depletion was, the stronger the work alienation. Our results supported previous studies that showed that empathy was negatively correlated with ego depletion and work alienation, while ego depletion was positively correlated with work alienation ( Finley et al, 2017 ; Delgado Bolton et al, 2022 ). Nurses with high empathy could correctly perceive their own emotions and those of their patients, reasonably and effectively regulate their cognition, emotion, and behavior, reduce their energy consumption, get along well with patients, and experience a better sense of value and achievement in their work.…”
Section: Discussionsupporting
confidence: 92%
“…), master digitization, understand cost-efficiency-based management, etc. It is recommended that the defensive, self-protective behavior be replaced with continuous learning [ 2 , 3 ], regardless of the speciality and the accumulated work experience, supplementing such learning with an important component of interpersonal empathy, which would increase the safety of patients [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Doctors, based on the skills and abilities acquired by completing medical studies, obtain the title of doctor/specialist and the right and ability to provide and communicate information within the limits of the acquired skills [ 1 ]. The quantity, quality, and veracity of such information are directly proportional to a doctor’s level of awareness of the need for continuous development and learning [ 2 , 3 , 4 ], a process that must guide the professional path of each doctor.…”
Section: Introductionmentioning
confidence: 99%
“…This instrument has been initially tested in professionals from different disciplines in Spain and in Latin American countries, including Ecuador, showing good psychometric properties [ 25 ]. In physicians, this instrument has been previously proven with samples from Spain [ 7 ] and Latin American [ 4 , 10 , 11 , 26 ] countries with excellent results.…”
Section: Methodsmentioning
confidence: 99%
“…Before the COVID-19 pandemic began in 2020, being a physician in a public institution in low-to-middle income countries (LMICs) implied working in harsh working environments usually with scarce or inadequately distributed resources and with work overload. In Latin America, where this situation has being reported in recent studies [ 4 , 10 , 11 ], cognitive empathy has been demonstrated to play a key role in the prevention of work distress in those physicians.…”
Section: Introductionmentioning
confidence: 99%